Productive and unproductive behaviours of employees in an engineering company : An exploration using critical incident technique / Nur Salfiah Muthazrah Bujang...[et.al] - Bujang, Nur Salfiah Muthazrah; Gilbert Taylor, Noor Cara Adila (2018)
Brooke Dockyard Engineering Works Corporation (BDEWC) is owned by the State Government of Sarawak under the Ministry of Infrastructure Development and Communications and now it is growing as an integrated engineering corporation, building customized products with no compromise on the standard of safety and quality. Therefore, ensuring its own employees' productivity level is its major concern as it also needs to fulfill its International Organization for Standardization (ISO) requirement.